Structural covariance mapping delineates medial and medio-lateral temporal networks in déjà vu - Shaw, Daniel Joel; Mareček, Radek; Brázdil, Milan (Brain imaging and behavior, 2016)
Déjà vu (DV) is an eerie phenomenon experienced frequently as an aura of temporal lobe epilepsy, but also reported commonly by healthy individuals. The former pathological manifestation appears to result from aberrant neural activity among brain structures within the medial temporal lobes. Recent studies also implicate medial temporal brain structures in the non-pathological experience of DV, but as one element of a diffuse neuroanatomical correlate; it remains to be seen if neural activity among the medial temporal lobes also underlies this benign manifestation. The present study set out to investigate this. Due to its unpredictable and infrequent occurrence, however, non-pathological DV does not lend itself easily to functional neuroimaging. Instead, we draw on research showing that brain structure covaries among regions that interact frequently as nodes of functional networks. Specifically, we assessed whether grey-matter covariance among structures implicated in non-pathological DV differs according to the frequency with which the phenomenon is experienced. This revealed two diverging patterns of structural covariation: Among the first, comprised primarily of medial temporal structures and the caudate, grey-matter volume becomes more positively correlated with higher frequency of DV experience. The second pattern encompasses medial and lateral temporal structures, among which greater DV frequency is associated with more negatively correlated grey matter. Using a meta-analytic method of co-activation mapping, we demonstrate a higher probability of functional interactions among brain structures constituting the former pattern, particularly during memory-related processes. Our findings suggest that altered neural signalling within memory-related medial temporal brain structures underlies both pathological and non-pathological DV.
Keywords: Déjà vu; Least-Squares Analysis; Magnetic Resonance Imaging; magnetická rezonanční tomografie; Humans; Grey matter; lidé středního věku; mapování mozku; Deja Vu; Structural co-variance; epilepsie temporálního laloku; Female; mladý dospělý; dospělí; Temporal Lobe; spánkový lalok; nucleus caudatus; lidé; Meta-Analysis as Topic; Databases as Topic; Brain Mapping; Adult; Caudate Nucleus; nervové dráhy; Gray Matter; ženské pohlaví; Neural Pathways; Male; déja vu; Middle Aged; metoda nejmenších čtverců; šedá hmota; Epilepsy, Temporal Lobe; Meta-analytic connectivity modelling; Young Adult; databáze jako téma; Memory; mužské pohlaví; metaanalýza jako téma